Shifting Domestic Roles In The Household And Their Influence On Children's Education In Matang Sagoe Village Peusangan Sub-District Bireuen District - Hasanah, Uswatun; Mardhiah, Ainal; Hayati, Hayati; Zubaidah, Zubaidah; Nurbayani, Nurbayani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
The shift in domestic roles in Matang Sagoe indicates a shift towards a more equal division of responsibilities between husband and wife. This has various impacts on children's education . Some Matang Sagoe people still hold fast to traditional values, where mothers are expected to remain the main caregivers and managers of the household, while fathers are the main breadwinners. This study uses a qualitative method with a field research approach. Data collection techniques consist of in-depth interviews, participatory observation and documentation. The results of the study show that 1). The form of shifting domestic roles in households on children's education in Matang Sagoe Village Peusangan Sub-District Bireuen District is from traditional roles to more flexible roles, working mothers and a more equal division of tasks. 2). The influence of shifting domestic roles in households on children's education in Matang Sagoe Village Peusangan Sub-District Bireuen District is on increasing father involvement in children's education, the role of working mothers and their influence, higher child independence and the negative influence of limited time. 3). Factors of shifting domestic roles in households on children's education in Matang Sagoe Village Peusangan Sub-District Bireuen District are economic changes, education levels and cultural and social influences